PRODUKSI RISIKO INDUSTRI FAST FASHION DALAM FENOMENA THRIFTING DI KOTA DENPASAR - Prabaswari, Gusti Ayu Yogiana; Punia, I Nengah; Krisna Aditya, I.G.N Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT This study aims to describe and analyze further about thrifting phenomenon in relation to the environmental risks production of fast fashion industry. The approach used in this study is qualitative with descriptive exploratory types. The teory used is the risk society by Ulrich Beck. The result of this study shows that fast fashion industry risks in Kota Denpasar capable of rising environmental awareness for the majority of the informants. Thrifting is believed can make clothes lifespan longer and to minimize the risks by fast fashion consumption. Furthermore, there are three aspects that urge consumers to thrift those are economic aspect, environmental aspect, and individual aspect. In addition, the existence of health impact by wearing second hand clothes turns out doesn’t change consumer perception about their second hand consumption. Keywords: second hand clothes, thrifting, fast fashion, risk production, environmental awareness